INTEGRASI PENDIDIKANQKARAKTERQPADAQPEMBELAJARAN TEMATIKQKELAS III DI UPT SDQNEGERI 309 GRESIK - Eka Zuliana; Mohammad Afifulloh; Fita Mustafida (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2021)
This examination expects to depict the integration of character education in thematic learning which includes planning, implementation and evaluation in third grade thematic learning at UPT SD Negeri 309 Gresik. The data in this study were collected through interviews, documentation and observation. This analysis data used the Milles and Humberman model, in particular information buildup, information show, and making determinations. The strategy of checking the legitimacy of the information by utilizing triangulation strategies. The outcomes showed. That character education which was integrated into thematic learning at UPT SD Negeri 309 Gresik was good in planning stage, the teacher has included character values that will be integrated in learning in the lesson plans. This research was conducted at UPT SD Negeri 309 Gresik in June 2021. Kata kunci: Integrasion, character building, thematic learning.